Rethinking Urban and Food Policies to Improve Citizens Safety After COVID-19 Pandemic - Galimberti, Andrea; Cena, Hellas; Campone, Luca; Ferri, Emanuele; Dell'Agli, Mario; Sangiovanni, Enrico; Belingheri, Michael; Riva, Michele Augusto; Casiraghi, Maurizio; Labra, Massimo (Frontiers in Nutrition, 2020)
The ongoing pandemic caused by the coronavirus disease 2019 (COVID-19) is literally changing the world. From December 2019 to date, more than 22 million cases have been reported worldwide and global health institutions are acting to slow down the virus transmission and are looking for possible prevention strategies in case of a new outbreak. As in other endemic or pandemic phenomena, the issues mostly covered by scientific and media attention are related to the diagnostic and therapeutic approach of COVID-19. However, a still neglected issue regards the adoption of a more systemic approach considering the close connection among the infection, the environment, and human behaviors, including the role of diet and urban management. To shed light on this issue, we brought together a faculty group involving experts in environment and biodiversity, food safety, human nutrition and behavior, bioprospecting, as well as medical doctors having a deep knowledge of the complex historical relationship between humanity and vector-borne infections. Two main aspects emerged: i) the scientific community should start sharing social actions and policy advocacy based on the assumption that human health strongly depends upon sustainable exploitation of natural resources in populated areas; ii) the specific strategic role of the cities in developing sustainable food systems and promoting healthy dietary patterns. Definitely, some priority issues should be addressed to achieve these goals, such as global efforts to increase food safety and security, which would benefit from urban and peri-urban agriculture enhancement, smallholder food producers support, and ecosystem services and local biodiversity maintenance.